Peningkatan Nilai Ekonomis dan Pencegahan Stunting Melalui Modifikasi Pengolahan Susu Kambing Etawa di Desa Pucung, Kismantoro, Wonogiri - Purwanta; Idham Bachtiar; Sundari, Onik Dwi (Direktorat Pengabdian kepada Masyarakat, 2024)
mountainous topography leads to the majority of the population being engaged in farming and animal husbandry. The livestock sector is prevalent in Pucung Village, with the most commonly raised animals being PE goats or Etawa crossbreeds. In order to optimize the outcomes of livestock farming in Pucung Village, the UGM Community Service and Student Creativity Program (KKN-PPM UGM) team implemented a work program of counseling and training on the production of processed products from goat milk, namely pasteurized goat milk and Etawa goat milk ice cream. The aim of this work program is to diversify livestock processed products into products that are more desirable to consumers. The nutritious content of Etawa goat milk, beneficial for health, can help reduce stunting in the Kismantoro area. Furthermore, both products can enhance the local economy if produced and marketed sustainably. The method used in this activity involves research through several stages including observation, literature study, coordination meetings, material preparation, program implementation, and evaluation.